Determinan Profitabilitas BPRS di Indonesia: Perspektif Nisbah Bagi Hasil Mudharabah, Musyarakah, dan Murabahah Tahun 2010-2021 - Fitria Andriany; Muhammad Dayyan (JIM: Jurnal Ilmiah Mahasiswa, 2025)
This study aims to analyze the influence of profit-sharing ratios in Islamic financing products—including mudharabah, musyarakah, and murabahah—on Return on Assets (ROA) of Islamic Rural Banks (BPRS) in Indonesia during the 2010-2021 period. The research method employed is quantitative with a total sampling approach, where the entire population of BPRS operating in 2021—totaling 163 entities—was included as samples. Time-series data spanning 10 years (2012-2021) was collected from financial reports published by the Financial Services Authority (OJK). The research findings reveal varied outcomes: partially, the mudharabah profit-sharing ratio shows no significant effect on ROA (sig. 0.914 > 0.05), while both musyarakah (sig. 0.000 < 0.05) and murabahah (sig. 0.005 < 0.05) demonstrate positive and significant influences. Simultaneously, all three financing variables collectively exert a significant effect on ROA (F-test sig. 0.002 < 0.05). The research implications indicate that optimal financing composition strategies—with emphasis on musyarakah and murabahah—can be key to enhancing BPRS profitability. These findings suggest the need for evaluating the effectiveness of mudharabah schemes in contributing to BPRS' financial performance.